ABIDS-WSN: UM FRAMEWORK DE DETECÇÃO DE INTRUSÃO EM REDES DE SENSORES SEM FIO ORIENTADO POR AGENTES INTELIGENTES. - PIRES, Higo Fellipe Silva (2017)
Lately, there has been a significant advance in several technologies directly or indirectly related to Ubiquitous Computing. Among them, the technology of Wireless Sensor Networks (WSNs) can be mentioned. Having its space in the current scenario, the use of wireless sensors extends into various branches of human activity: industrial monitoring, smart houses, medical and military applications. However, several shortcomings and limitations in wireless sensors can be noted: limited hardware, energy and computational capacity are points that are always treated by those who work with such devices. As for these devices, there is, besides the factors already mentioned, an important concern regarding their safety. As with other devices, for these threats to be at least mitigated, it is necessary to create layers of security. One of these layers may be formed by Intrusion Detection Systems (IDS). However, due to the aforementioned hardware restriction of the sensors, the development of IDSs - as well as any other application - for such devices should assume such characteristics. As for IDSs, there are some aspects that need to be taken into account, especially flexibility, efficiency and adaptability to new situations. A paradigm that facilitates the implementation of such capabilities is the Intelligent Agents. Therefore, this paper describes the proposition of a framework for intrusion detection in WSNs based on intelligent agents.